The development and evaluation of a unit of high school English dealing with Newfoundland dialect and standard English - Cooper, Varrick, 1951- (1982)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1982. Education Bibliography: leaves [111]-114. -- QEII has photocopy. The purpose of this internship was to develop and evaluate a unit of curriculum and instruction for senior high school English students in Newfoundland. -- The unit, entitled Two Varieties of English, analyzes the vocabulary, pronunciation and grammar of both Newfoundland dialect and standard English and the way each has developed. Objective 1 of the unit, therefore, was to give the students who studied the unit, a Grade Eleven English class at Coaker Academy, New World Island, an understanding of the history and structure of Newfoundland dialect and standard English. The degree to which this objective was attained was determined by the administering of a post-unit quiz. -- Two Varieties of English also deals with both popular and learned attitudes to Newfoundland dialect and standard English. The unit agrees with the linguists who have studied the two varieties of English that Newfoundland dialect is a legitimate, effective means of communication for certain purposes, audiences, and settings. At the same time, it recognizes the necessary role that standard English has as the accepted uniform means of communication in the larger community of divergent linguistic practice where dialectal variations would impede communication. It acknowledges the barriers to economic and social advancement that are erected if one fails to use standard English in certain kinds of communication situations. The unit advises that it is neither necessary to accept these barriers nor to reject the language of one's family, friends, and community. The unit proposes as the solution to this dilemma bidialectalism, the use of Newfoundland dialect or standard English depending on which is more suitable for a particular communication situation. -- Objective 2 of the unit, therefore, was to promote rational attitudes toward Newfoundland dialect and standard English. The degree to which this objective was achieved was determined by comparing the results of a pre-test and post-test of students’ attitudes to Newfoundland dialect and standard English. The same Likert-type instrument was used for both the pre-test and post-test. It consisted of twenty-five statements each of which expressed an opinion about Newfoundland dialect or standard English or both. -- Data as generated would appear to support the following conclusions: -- 1. Objective 1 was achieved to a high degree. -- 2. Objective 2 was achieved to a fairly high degree.